Menggali potensi generasi z: strategi efektif memasyarakatkan investasi syariah - HANIFATURASYDA, ARFINA (Maliki Interdisciplinary Journal, 2025)
Generation Z has great potential to become active investors, especially in sharia investments. However, their participation in sharia investment is still relatively low. This research aims to explore the potential of Generation Z in sharia investment and identify effective strategies in popularizing the concept of sharia investment. The research methods used include document study, literature study and social media analysis to observe Generation Z's perceptions, challenges and interest in sharia investment. The research results show that factors such as Islamic financial literacy, risk preferences, and technology accessibility play an important role in determining Generation Z's interest in Islamic investment. With the right approach, Generation Z has the potential to become a major contributor in the Islamic finance industry.